Beyond the screen: Investigating the added value of realism enabled by the metaverse in digital game-based entrepreneurial learning - Anna Wenzel; Jan-Martin Geiger; Andreas Liening (Computers in Human Behavior Reports)
Despite growing research interest in the educational potential of contemporary metaverse platforms, especially their immersive 3D open-world designs and prospects for experiential and collaborative learning, there is still limited evidence regarding their added value compared to existing 2D digital game-based learning media. This experimental study investigates a novel 3D frontend of a well-established business simulation game (BSG) in higher education, implemented using Roblox as a contemporary metaverse platform. The focus lies on students’ gameful experiences and entrepreneurial learning outcomes. Using a between-subject longitudinal design over five weeks, one group of students (n = 58) engaged with the 3D virtual world, while the control group (n = 42) used the original 2D frontend. Survey data were collected at baseline, weekly during the BSG, after completing the BSG, and at the final exam at the end of the semester. Linear mixed-effects modeling revealed significantly higher levels of gameful experience in the 3D condition across the dimensions of Accomplishment, Challenge, Competition, Social Experience, and Playfulness, while controlling for time, prior knowledge, game-related and content-related intentions, and game success. Although differences in entrepreneurial learning outcomes were not statistically significant, multiple regression analyses revealed that students in the 3D condition achieved slightly higher final scores in entrepreneurial knowledge. The study concludes with practical implications for digital pedagogy in higher education and outlines directions for future research on immersive 3D digital game-based learning.